Training Aid Development for Twist on Artistic Gymnastics Competition in Pemalang Regency (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2020)
The study aimed to develop a twist training aid and find out the effectiveness of the twist training aid in increasing somersault twist motion used in training for junior and senior athletes. This study uses a model development method with a qualitative approach. The main procedure in research and development consists of six steps, namely: analyzing the product to be developed, developing the initial product, expert validation, product revision, large-scale trial, product end. The results of the study concluded that the development of twist training aids on the artistic gymnastics race by producing Atlantis products was well categorized and suitable for use as a somersault twist motion training aid in artistic gymnastics for junior athletes, and senior athletes, could improve skills in somersault twist and somersault twist for junior athletes and senior athletes, make it easier for coaches to provide assistance in somersault twist and somersault twist exercises for junior and senior athletes.